Mafias and Firms - Jaime Arellano-Bover; Marco De Simoni; Luigi Guiso; Rocco Macchiavello; Domenico J. Marchetti; Mounu Prem (Center for Economic Studies and ifo Institute (CESifo), 2024)
Infiltration of the legal economy by criminal organizations (OCGs) is potentially significant, though how pervasive remains uncertain. Beyond the volume, the motives driving infiltration are of serious policy concern. We introduce a conceptual framework to differentiate between OCGs' motives for infiltrating legal firms and validate it using new data from the Italian Financial Intelligence Unit. About 2% of Italian firms appear to have links with OCGs, with three primary motives. Firms established by OCGs are predominantly used for criminal activities (functional motive). Medium-sized firms, often infiltrated post-creation, primarily reflect a competitive motive, wherein criminal activities benefit the firm. Lastly, large, well-established firms remain separate from criminal activities and are used for pecuniary and non-pecuniary returns, such as to establish political connections (pure motive). This so far unnoticed motive accounts for a substantial share of OCGs' infiltration.
Keywords: G30; L20; K40; 330; organized crime; legal economy; firms; infiltration